The first complete chloroplast genome of Thalictrum fargesii: insights into phylogeny and species identification - Chen, Shixi; Safiul Azam, Fardous Mohammad; Akter, Mst. Lovely; Ao, Li; Zou, Yuanchao; Qian, Ye (Frontiers in Plant Science, 2024)
Thalictrum fargesii is a medicinal plant belonging to the genus Thalictrum of the Ranunculaceae family and has been used in herbal medicine in the Himalayan region of China and India. The species is a taxonomically challenging species because of its morphological similarities to other species within the genus. Thus, herbal drugs from this species are frequently adulterated, substituted, or mixed with other species, thereby endangering consumer safety. The present study aimed to sequence and assemble the entire chloroplast (cp) genome of T. fargesii using the Illumina HiSeq 2500 platform for a better understanding of its genomic architecture, gene composition, and phylogenetic relationships within the Thalictrum. The cp genome was 155,929 bp long and contained large single-copy (85,395 bp) and small single-copy (17,576 bp) regions, which were segregated by a pair of inverted repeat regions (26,479 bp) to form a quadripartite structure. This cp genome contains 133 genes, including 88 protein-coding genes (PCGs), 37 tRNA genes, and eight rRNA genes. Additionally, this genome contains 64 codons that encode 20 amino acids; the most preferred amino acids are alanine and leucine. We identified 68 SSRs, 27 long repeats, and 242 high-confidence C-to-U RNA-editing sites in the cp genome. Moreover, we discovered seven divergent hotspot regions in the cp genome of T. fargesii, among which ndhD-psaC and rpl16-rps3 might be useful to develop molecular markers for identifying ethnodrug species and their contaminants. A comparative study with other eight species in the genus revealed that pafI and rps19 have highly variable sites in T. fargesii’s cp genome. Additionally, two special features, i) the shortest length of the ycf1 gene at the IRA-SSC boundary, and ii) the distance between the rps19 fragment and trnH at the IRA-LSC junction, have distinguished the cp genome of T. fargesii from those of other species within the genus. Furthermore, phylogenetic analysis revealed that T. fargesii is closely related to T. tenue and T. petaloidium. Considering all these evidences, our findings offer crucial molecular and evolutionary information that could play a significant role in further species identification, evolution, and phylogenetic research on T. fargesii.